Analisis Metode Pemberdayaan Komunitas Berbasis Digital melalui Youth Idea Community (YIC) Indonesia - Alwasili, Abdulah; Rahmawati, Tia; Rahmatullah, Muhammad Arif; Febriyanti, Melani; Fadila, Rifka (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study examines the positive contribution of Youth Idea Community (YIC) Indonesia in empowering digital-based communities through development methods, active innovation, and positive collaboration. This community empowerment initiative focuses on improving digital literacy, creativity, and social participation through programs that include education, social issues, general knowledge, and literacy improvement. By implementing a three-pillar impact-ready scheme (development programs, learning, and collaboration) and the Zenius Learning model, this initiative has succeeded in creating an ecosystem that encourages independence and self-confidence. The findings in this study indicate that a technology-based collaborative approach can effectively address geographical and cultural challenges while increasing the capacity of the younger generation to thrive in the digital era.